Investing in Threatened Species Conservation: Does Corruption Outweigh Purchasing Power? - Garnett, Stephen T. (Public Library of Science, 2011)
In many sectors, freedom in capital flow has allowed optimization of investment returns through choosing sites that provide the best value for money. These returns, however, can be compromised in countries where corruption is prevalent. We assessed where the best value for money might be obtained for investment in threatened species that occur at a single site, when taking into account corruption. We found that the influence of corruption on potential investment decisions was outweighed by the likely value for money in terms of pricing parity. Nevertheless global conservation is likely to get best returns in terms of threatened species security by investing in “honest” countries than in corrupt ones, particularly those with a high cost of living.